GROWTH RESPONSE AND SURVIVAL OF NILE TILAPIA (Oreochromis niloticus) FED STEROID HORMONE AND PAWPAW SEED (Carica papaya) MEAL BASED DIET. - OROSE, E; WOKE, G. N; BEKIBELE, D.O (Nigerian Journal of Fisheries, 2018)
This study was conducted to evaluate the effect of wet testes of bull (Bos. indicus), boar (Sus. domesticus), combination of bull and mud catfish testes (B. indicus / C. gariepinus) and pawpaw seed powder (Carica papaya) on the growth and survival rate of O. niloticus fry in an indoor experimental ponds. Fifty five fry were assigned randomly to five experimental ponds in triplicate. The feed (composed of soya-bean, fish meal, wheat bran, cassava flour (garri)) in Pond one (G1), Pond two (G2), Pond three (G3), Pond four (G4), and Pond five (G5) was formulated by adding 17αmethyl-testosterone (0.06g), wet testes from bull (17.47g), boar (25.59g), combination of bull and catfish (20.48g) at a ratio of 80:20 and pawpaw seed powder (20g) respectively per kg of feed. The growth and survival rate of fry in G1, G2, G3, G4 and G5 was (3.59±0.09c& 72.33±7.22b, 4.00±0.22bc& 92.33±5.78a, 5.12±0.09a& 95.67±1.45a,4.33±0.41bc& 97.00±2.08a , 4.70±0.07ab & 98.07±3.03a) respectively with significant (p<0.05) difference. From theresult, it appears that the feed formulation in G3 was more favourable to the growth of tilapia compared to theformulation in G5, G4, G2 and G1 whereas the feed formulation in G5 had the highest survival rate.